Mind Mapping on Students’ Writing Descriptive Text - Wulansari Panggabean; Fitriadi Lubis; Rayendriani Fahmei Lubis (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
This research focused on students’ writing descriptive text by using mind mapping strategy. The research was experimental research that uses one group pre-test and post-test design with 32 students in experimental and control class at Grade VIII Students of SMP N 6 Padangsidimpuan. The data were collected from students’ writing test that consists of 32 students for experimental class and 32 students also for control class. The result of the research have found from t-test, which is t-count higher than t-table 6.22 ˃ 1.66. It was concluded that mind mapping strategy has a significant effect on the writing descriptive text of students.